Co-Pyrolysis of EFB and UPCO over Nickel Oxide Loaded HZSM-5: A Comparative Co-Pyrolysis Study via Thermogravimetric Analyser and Fixed-Bed Reactor - Balasundram, Vekes; Abdul Manaf, Norhuda; Ibrahim, Norazana; Isha, Ruzinah; Gopakumar, Suchithra Thangalazhy; Pham, Le Kim Hoang (International Journal of Integrated Engineering, 2025)
The abundance of empty fruit bunches (EFB) in Malaysia, which were once discarded as waste, has recently been recognized as a potential source for biofuel production. The main objective of the present work is to evaluate the impact of nickel oxide-loaded HZSM-5 (NiO/HZSM-5) on the co-pyrolysis of EFB and Used Palm Cooking Oil (UPCO) via thermogravimetric analyser (TGA) and fixed-bed reactor separately. The NiO/HZSM-5 was prepared via incipient wetness impregnation method and characterized for physicochemical properties. First, for co-pyrolysis via TGA, the pyrolysis temperature for all samples was fixed from 30 to 700°C. The mass loading was fixed for EFB, EFB-UPCO, EFB-HZSM-5, EFB-UPCO-HZSM-5, EFB-UPCO-(1%)NiO/HZSM-5. Second, for co-pyrolysis via fixed-bed reactor, the temperature was fixed at 600°C. From TGA results, the usage of UPCO for pyrolysis with EFB has generated higher mass loss (99.73%) compared to pyrolysis of EFB and EFB over HZSM-5 at 90.54% and 73.33% respectively. From the fixed-bed reactor, pyrolysis of EFB has generated no hydrocarbons in biofuel. The loading of UPCO has increased the hydrocarbon yield by 64.90%. Catalytic co-pyrolysis over Ni/HZSM-5 had proved to increase oil yield and enhance hydrocarbons. The pyrolysis of EFB with UPCO provides an approach in which UPCO can serve as a hydrogen source to enhance the biofuel quality, and NiO enhances the cracking of the oxygenated vapours into hydrocarbons.